2011
DOI: 10.1002/jcb.23200
|View full text |Cite
|
Sign up to set email alerts
|

The retinol signaling pathway in mouse pluripotent P19 cells

Abstract: atRA (all-trans-retinoic acid), the active metabolite of retinol (vitamin A), is essential for embryogenesis and maintenance of cellular phenotype in adults. Chemicals that interfere with the metabolism of retinol to atRA, therefore, are a human health concern. During development of a screen for disruptors of this signaling pathway, we investigated whether the mouse pluripotent P19 cell metabolizes retinol to atRA and thus can be used in a cell-based screen for disruptors of the pathway. We found that retinol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 50 publications
0
32
0
Order By: Relevance
“…Interestingly, mRNA for the extracellular ROL carrier (Rbp4) was present in both NE-4C and RGl cells regardless of the stage of their development. Rbp4 expression may contribute to the regulation of vitamin A availability in the proximate environment of neural stem/progenitor cells [27,28] or developing/mature neurons [43,54]. Both retinoid sensitivity and production by differentiating neural stem cells highly depend on the cellular composition of the cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mRNA for the extracellular ROL carrier (Rbp4) was present in both NE-4C and RGl cells regardless of the stage of their development. Rbp4 expression may contribute to the regulation of vitamin A availability in the proximate environment of neural stem/progenitor cells [27,28] or developing/mature neurons [43,54]. Both retinoid sensitivity and production by differentiating neural stem cells highly depend on the cellular composition of the cultures.…”
Section: Discussionmentioning
confidence: 99%
“…P19 cells and their derivate P19CL6 cells have already been used to identify the cardiomyogenic potential of single substances and to elucidate signaling pathways. Chen and Reese [2011] made use of P19 cells to study the retinol-signaling pathway and Danalache et al [2010] found a novel cardiomyogenic peptide with its help. Sadek et al [2008] used P19CL6 cells to identify small molecules involved in cardiac fate by screening a chemical library for activators of the signature gene NKX2-5.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] atRA is also known to be capable of inducing embryonic stem cells and embryonal carcinoma cells to differentiate into neural lineages. 12,13) atRA functions as the activating ligand for retinoic acid receptors (RARs), and atRA-RAR complexes regulate the expression of over 500 target genes as a transcription factor. 11,[13][14][15][16] RARs are a member of the nuclear receptor superfamily, 17,18) and consist of three isotypes: α, β, and γ.…”
Section: Tal2mentioning
confidence: 99%
“…12,13) atRA functions as the activating ligand for retinoic acid receptors (RARs), and atRA-RAR complexes regulate the expression of over 500 target genes as a transcription factor. 11,[13][14][15][16] RARs are a member of the nuclear receptor superfamily, 17,18) and consist of three isotypes: α, β, and γ. In response to atRA signaling, RARs occupy characteristic retinoic acid response elements (RAREs) located in the promoter regions of target genes.…”
Section: Tal2mentioning
confidence: 99%